Proletarização e mal-estar docente nas universidades públicas: uma perspectiva crítica - Solange Martins Oliveira Magalhães (EccoS – Revista Científica)
The extent and density of the effects of neoliberal logic has transformed public university becoming the victim of numerous retaliation, that the distance from the possibility of promoting quality education, with a sense of identity with social justice and democratic citizenship. This same neoliberal logic has also impacted the teaching work, generating the teacher malaise. Based on a dialectic, a survey was conducted with 20 teachers, trying to analyze the issue of malaise that has been around teaching in public universities. It was found that the approach of teachers working conditions proletarian, asserts a state of pity and sorrow, but also manifested a contradiction between the rapid pace of change in its work processes that are subject to public university, and the desire to respond the demands made upon them to get the recognition from their peers and institutional. Discloses a conflict from which signals that among many of the issues generating unease teacher, this is one more to be faced, because we understand that this conflict is generating more individual effort in solving the tasks, increasing personal investment to the detriment of the collective, which prevents collective work.